Bilayer BaSnO3 thin film transistors on silicon substrates. Issue 15 (25th March 2020) - Du, Wenhan; Nguyen, Anh Chien; John, Rohit Abraham; Yang, Jing Jing; Kulkarni, Mohit Rameshchandra; López-Mena, Edgar R.; Nirmal, Amoolya; Mathews, Nripan
Abstract : Barium tin oxide BaSnO3 (BSO) is a novel wide-bandgap semiconducting material with high electron mobility and is considered as a promising alternative to indium-containing amorphous oxide semiconductors. Abstract : Barium tin oxide BaSnO3 (BSO) is a novel wide-bandgap semiconducting material with high electron mobility and is considered as a promising alternative to indium-containing amorphous oxide semiconductors. Herein, high-performance BSO thin film transistors (TFTs) on non-epitaxial substrates by forming a unique bilayer structure via sputtering are demonstrated. Synergistic control over the deposition rate and post-annealing temperatures result in precise formation and modulation of oxygen vacancies, culminating in insulating and semiconducting BaSnO3 fractions within the bilayer structure. These devices exhibit thermally activated charge transport properties with a field effect mobility of 0.75 cm 2 V −1 s −1 and an I on / I off ratio of 10 4 . These novel BSO TFT devices are stable for at least 20 days with moderate storage conditions (room temperature, 30–40% humidity, air conditions), thus paving the way for the facile fabrication of high-performance indium-free switching devices.